صورة التقدم في الفكر الإسلامي الحديث : The Illustration of Progress in the Discourse of Islamic Thought in Modern Era - Benboudina , Amar (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
Modern-day thinkers have different trends on the idea of progress (al-taqaddum), which has seemed to swing between different approaches in terms of theoretical, reference, purpose, depth, structure of analysis, and model formation. This study aims to understand the idea of progress in Islamic thought by some Islamic thinkers. Its objective is to discover an evolution of this idea based on Islamic thinkers’ analysis on the condition of Arab Muslims compared to Europeans. Thus, it puts forward a recommendation by some of the contemporary Islamic thinkers to follow the development of developed nations’ as well as determining the orientations and conditions for taking advantage of what is positive from them, in the hope that such changes provide at least minimum conditions for national progress. The study concludes that the best path towards the Muslims progress is that they should share the same values of progress, develop a diversity of notions including cultural plurality, awareness of historical collection, ready to progress from various aspects whether political, economic, and social, and create a high awareness on historical defeat on the backwardness of Muslims today.